Synthesis, characterization, in vitro bioactivity and antimicrobial activity of magnesium and nickel doped silicate hydroxyapatite - Alshemary, Ammar Z. (Elsevier Ltd., 2015)
Incorporation of Mg2+, Ni2+, and SiO44− ions into hydroxyapatite (HA) structure was successfully carried out by microwave assisted wet precipitation method to furnish Ca10−x−yMgxNiy(PO4)6−z(SiO4)z(OH)2−z□z. Incorporation of silicate ions into the HA structure led to the increase in HA lattice parameters, while incorporation of (Mg2+ and Ni2+) ions led to the reduction of lattice parameters and crystallite size of silicate doped HA. Optical analysis showed a distinct red shift upon increase in Ni2+ concentration due to the decrease in particle size. Dissolution of samples in simulated body fluid showed that the incorporation of Mg2+, Ni2+ and SiO44− in HA structure resulted in considerable increase in the in vitro dissolution of HA. The prepared samples promoted exceptional in vitro apatite growth over 14 days with Ca/P ratio close to 1.67. The analysis of in vitro antibacterial activity against E. coli and P. aeruginosa revealed that the Ni2+ containing samples possessed good antibacterial properties.